1999
DOI: 10.1016/s0921-5093(99)00307-x
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced martensitic transformations in NiTi and NiTi–TiC composites investigated by neutron diffraction

Abstract: Superelastic NiTi (51.0 at.% Ni) specimens reinforced with 0, 10 and 20 vol.% TiC particles were deformed under uniaxial compression while neutron diffraction spectra were collected. The experiments yielded in-situ measurements of the thermoelastic stress-induced transformation. The evolution of austenite/martensite phase fractions and of elastic strains in the reinforcing TiC particles and the austenite matrix were obtained by Rietveld refinement [1] during the loading cycle as the austenite transforms to mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 24 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…This late hardening behavior is also found in Zr and Mg [3,6] and is frequently associated with deformation twinning or a stress-induced phase transformation as in superelastic nickel-titanium alloys. [26] Again, the calculation satisfactorily reproduces the observed mechanical response, including the increased hardening above 15 pct deformation. Reduced or elevated temperature testing (75 or 673 K) does not significantly affect the yield point of the beryllium in any of the texture-load combinations; however, the subsequent hardening behavior is a strong function of the temperature.…”
Section: Visco-plastic Self-consistent Modelingsupporting
confidence: 59%
“…This late hardening behavior is also found in Zr and Mg [3,6] and is frequently associated with deformation twinning or a stress-induced phase transformation as in superelastic nickel-titanium alloys. [26] Again, the calculation satisfactorily reproduces the observed mechanical response, including the increased hardening above 15 pct deformation. Reduced or elevated temperature testing (75 or 673 K) does not significantly affect the yield point of the beryllium in any of the texture-load combinations; however, the subsequent hardening behavior is a strong function of the temperature.…”
Section: Visco-plastic Self-consistent Modelingsupporting
confidence: 59%
“…The lack of significant fatigue differences is surprising since the uniaxial tensile stress-strain response of NiTi and NiTi-TiC are significantly different, with the composite showing lower ductility and higher twinning stresses. This could be due to a combination of factors such as microcracking, crack-deflection and the accommodation observed previously in shape-memory and superelastic composites [8,12,25]. Thus, the reinforcement concept can be used, for dilute concentrations at least, to tailor properties such as elastic modulus and transformation temperatures in NiTi without altering their fatigue crack growth characteristics.…”
Section: Discussionmentioning
confidence: 95%
“…Eshelby's inclusion theory was used to determine the residual stress due to the thermal expansion mismatch between the matrix and TiC [25,26]. The matrix has a mean tensile stress of 26 and 51 MPa (for NiTi -10TiC and NiTi-20TiC, respectively) due to this mismatch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about the phase-stress partition in the MMCs having the matrix exhibiting alternative deformation mechanisms (e.g., stress-induced martensitic transformation (SIMT) or mechanical twinning). [8][9][10] Here, the phase-stress partition in a NbTi/NiTi nanocomposite where the matrix is capable of deforming by SIMT was studied by using in situ synchrotron x-ray diffraction during tensile loading/unloading. It was found that, after the initial elastic deformation, the stress carried by the NbTi nanowires increased significantly while the stress taken by the NiTi matrix decreased with increasing macroscopic strain, which is different from that previously reported in the MMCs.…”
Section: Phase-stress Partition and Stress-induced Martensitic Transfmentioning
confidence: 99%